An indomitable beast : the remarkable journey of the jaguar - Rabinowitz, Alan, 1953- (Washington: Island Press, 2014)
The jaguar is one of the most mysterious and least-known big cats of the world. The largest cat in the Americas, it has survived an onslaught of environmental and human threats partly because of an evolutionary history unique among wild felines, but also because of a power and indomitable spirit so strong, the jaguar has shaped indigenous cultures and the beliefs of early civilizations on two continents. In An Indomitable Beast: The Remarkable Journey of the Jaguar, big-cat expert Alan Rabinowitz shares his own personal journey to conserve a species that, despite its past resilience, is now on a slide toward extinction if something is not done to preserve the pathways it prowls through an ever-changing, ever-shifting landscape dominated by humans. Rabinowitz reveals how he learned from newly available genetic data that the jaguar was a single species connected genetically throughout its entire range from Mexico to Argentina, making it unique among all other large carnivores in the world. In a mix of personal discovery and scientific inquiry, he sweeps his readers deep into the realm of the jaguar, offering fascinating accounts from the field. Enhanced with maps, tables, and color plates, An Indomitable Beast brings important new research to life for scientists, anthropologists, and animal lovers alike. This book is not only about jaguars, but also about tenacity and survival. From the jaguar we can learn better strategies for saving other species and also how to save ourselves when faced with immediate and long-term catastrophic changes to our environment. --
In the beginning... -- The Pleistocene jaguar corridor -- The first people of the jaguar -- When jaguars talked to man -- The conquest of jaguar land -- The killing grounds -- Into the jaguar's world -- Meals on the hoof -- Thinking to scale -- The underground railway of the jaguar -- Borderland jaguars -- In search of jaguarness -- The reluctant warrior -- Survival in a changing world.
Includes bibliographical references (pages 209-224) and index.
Keywords: Jaguar; Jaguar -- Social aspects; Jaguar -- Conservation; Wildlife conservation; Artenschutz; Jaguar; Wildtiermanagement